Differences in Total S-RBD Antibody SARS-CoV-2 Post-vaccination mRNA-1273 3rd Dosage (Heterologous Prime Booster) with Post-prime Vaccination Inactivated Whole Virus Two Doses (Homologous) in Health Personnel Surabaya H2LC Clinic - Deddy Hartanto; Jusak A. Nugraha; Theresia Indah Budhy (Universitas Airlangga, 2022)
SARS-CoV-2 cases have increased to 463,182,124 reported worldwide as of March 16, 2022 with a death toll of 6,079,600. Indonesia on March 17, 2022 has increased by 5,939,082 with a death toll of 153,212 (KPCPEN, 2022). SARS-CoV-2 is closely related to the coronavirus. One of the efforts made to prevent the risk of severe infection and reduce the death rate from the SARS-CoV-2 virus in Indonesia is a vaccination program. According to IDI (2021) cases of Covid-19 deaths are dominated by men (84%) and women (16%). Clinical trials in China and Brazil have shown that, the immunogenicity of two doses of the vaccine decreases over time and there is a decrease in low antibody concentrations after 6 months of running time. To overcome this potential, the Indonesian government gives priority to the 3rd vaccine booster. The purpose of this study was to analyze the comparison between the total antibody titer for the Spike-RBD (Receptor Binding Domain) SARS-CoV-2 protein after the 3rd dose of mRNA-1273 booster vaccination and post-vaccination of two doses of primary inactivated whole virus in health workers. This research was conducted by observation with a cohort approach. It was concluded that the results of the Mann Whitney two-sided test with a significance value of 0.000, the antibody titer correlation test results with gender had a value of 0.702 and -0.366 for the relationship between antibody titer and age. There was a significant difference between the primary vaccination dose of 2 doses of CoronaVac and the 3rd vaccination (booster) mRNA-1273, gender was strongly associated with S-RBD antibody titer and age was not associated with S-RBD antibody titer.